The College Campus, a Place of Learning, and a Place of Healing - Bashir, Huma A.; Francis, Joshua (Advances in Social Sciences Research Journal, 2024)
The COVID-19 pandemic and its aftermath have precipitated a marked increase in mental health needs among college students. Lockdowns, the sudden shift to remote learning, and social distancing mandates have compounded existing challenges, highlighting a trend that has evolved over the past two decades. Despite heightened demand for mental health support, colleges struggle to meet these needs amid the emotional aftermath of COVID-19 effectively. Recognizing the pivotal role of higher education institutions in shaping future leaders and addressing and enhancing the mental well-being of the college community is imperative to foster an environment conducive to learning and healing. This paper will review current literature on mental health within college campuses, examining multifaceted contributors to mental health challenges. Additionally, it aims to provide college practitioners with campus-wide strategies to support students, faculty, and staff, acknowledging the interconnectedness of the entire college community.